2020
DOI: 10.1021/acsphotonics.0c01201
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-Encoded Colocalization Microscopy at Cryogenic Temperatures

Abstract: Super-resolution localization microscopy is based on determining the positions of individual fluorescent markers in a sample. The major challenge in reaching an ever higher localization precision lies in the limited number of collected photons from single emitters. To tackle this issue, it has been shown that one can exploit the increased photostability at low temperatures, reaching localization precisions in the subnanometer range. Another crucial ingredient of single-molecule super-resolution imaging is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 44 publications
(72 reference statements)
1
19
0
Order By: Relevance
“…The histogram in Fig. 2d plots the distribution of the side lengths of the projected triangles and is well-described by a fit that considers the localization uncertainty as well as the random particle orientation (14). We determine a side length of 9.9 ± 0.6 nm in excellent agreement with the expected value.…”
Section: Polarcold On a Protein Trimersupporting
confidence: 61%
See 4 more Smart Citations
“…The histogram in Fig. 2d plots the distribution of the side lengths of the projected triangles and is well-described by a fit that considers the localization uncertainty as well as the random particle orientation (14). We determine a side length of 9.9 ± 0.6 nm in excellent agreement with the expected value.…”
Section: Polarcold On a Protein Trimersupporting
confidence: 61%
“…These studies have shown that PCNA forms a stable homo-trimer with a pseudo-hexameric shape. The stability and simple configuration of its structure makes PCNA a good model system for benchmarking our imaging methodology (14). To study Human PCNA with polarCOLD, we first fully labeled it via a His-tag linker on the N-terminal side of each subunit of the protein, forming an equilateral triangle (see method section and Fig.…”
Section: Polarcold On a Protein Trimermentioning
confidence: 99%
See 3 more Smart Citations